2005
DOI: 10.1136/bmj.38512.405440.8f
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in patients with tension-type headache: randomised controlled trial

Abstract: ISRCTN9737659.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
225
2
15

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 368 publications
(251 citation statements)
references
References 19 publications
9
225
2
15
Order By: Relevance
“…The lack of a difference between true and sham acupuncture in that study is in line with previous studies on different pain conditions and nausea caused by chemotherapy that demonstrated that true acupuncture is not more effective than sham acupuncture. However, all of these trials found a significant effect when groups were compared with a nonintervention group (8,22,28). These results indicate that sham acupuncture is not an inert method and highlight the methodological difficulties in the design of acupuncture trials.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The lack of a difference between true and sham acupuncture in that study is in line with previous studies on different pain conditions and nausea caused by chemotherapy that demonstrated that true acupuncture is not more effective than sham acupuncture. However, all of these trials found a significant effect when groups were compared with a nonintervention group (8,22,28). These results indicate that sham acupuncture is not an inert method and highlight the methodological difficulties in the design of acupuncture trials.…”
mentioning
confidence: 77%
“…In the present study, we did not use placebo or sham needles or minimal acupuncture, because studies suggest that that these are not inert treatments (8,22,23,28). Instead, our research question aimed to elucidate whether acupuncture is superior to the time and attention of meeting with the therapist.…”
Section: E940mentioning
confidence: 99%
“…The largest of these, which compared 132 verum patients with 63 sham controls [29], reported smaller overall decreases in headache days per month with no statistically significant differences between groups (41% verum vs. 37% sham, p=0.58 compared to 62% verum vs. 50% sham, p<0.001). The results of the other large randomised trial for chronic headache cannot be directly compared with ours as headache days was not an endpoint; nonetheless, a statistically significant difference was reported between patients randomised to acupuncture plus specialist headache care compared to those receiving specialist headache care alone [23].…”
Section: Discussionmentioning
confidence: 99%
“…Two unblinded (potential bias) trials reported benefit of acupuncture in treating acute headaches in comparison to normal standard of care or acute pharmaceutical intervention [57,67]. A systemic review and meta-analysis of 8 randomised controlled trials comparing acupuncture and sham procedure in TTH prophylaxis showed no significant benefit in the acupuncture arm in reducing headache frequency [68,69].…”
Section: Acupuncture Vs Acute Treatmentsmentioning
confidence: 99%
“…Melchart in 2005 [57] in their study on 270 patients evaluated the effectiveness of traditional acupuncture with superficial acupuncture or no treatment in patients with TTH. Patients were randomised to receive 12 sessions of either treatment.…”
Section: Earlier Trialsmentioning
confidence: 99%